Analisis Penerapan Standar Akuntansi Pemerintah Berbasis Akrual Pada Pemerintah Daerah Kabupaten Bungo - Dwi Siyamsih (Dhana, 2024)
The enactment of Law Number 71 of 2010 concerning accrual-based Government Accounting Standards (SAP) brought major changes to the financial reporting system in Indonesia. These changes are expected to provide a complete picture of the financial position, present actual information regarding rights and obligations, and be useful in evaluating performance. This research aims to find out how to analyze the implementation of accrual-based government accounting standards (SAP) at the Regional Financial and Asset Management Agency (BPKAD) of the Bungo Regency Government. The method used in this research is descriptive, namely a method that first collects existing data, compiles the data and analyzes the data so that it can provide solutions to problems in the research. Based on the research results, it shows that the Bungo Regency Regional Government has presented financial reports in accordance with Accrual-Based Government Accounting Standards (SAP) by obtaining an Opinion from the Financial Audit Agency (BPK), namely Fair With Exceptions (WDP) because the recognition of fixed assets in the Bungo Regency Balance Sheet has not yet been recognized. reflects the actual conditions so that the Financial Audit Agency (BPK) does not yet believe the validity of the assets.